2020
DOI: 10.1590/1678-4324-2020190302
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Fertilizer Effect on Growth, Polyphenols, and Endophytes in Two Baccharis Species

Abstract: In a climate change context, the buildup of CO2 will affect plant communities worldwide. This study evaluated the effects of CO2 enrichment on the development and defense of two Cerrado native species Baccharis dracunculifolia and B. platypoda and their associated endophytic fungi richness. The study took place in Open-Top Chambers, two with ambient CO2 concentration (~400 ppm) and two in an enriched environment (~800 ppm). Baccharis platypoda developed 20% more leaves under enriched CO2 conditions, whereas B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 76 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…Flavonoids are biosynthesized via the phenylpropanoid (PAL) pathway, which demands high levels of carbohydrates to operate. Therefore, if Flv content increased, it is reasonable to infer that other allelochemicals may have increased as well (O'Neill et al, 2010;Oki et al, 2020) and further hampered early instar performance (Zavala et al, 2013;Prasifka et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids are biosynthesized via the phenylpropanoid (PAL) pathway, which demands high levels of carbohydrates to operate. Therefore, if Flv content increased, it is reasonable to infer that other allelochemicals may have increased as well (O'Neill et al, 2010;Oki et al, 2020) and further hampered early instar performance (Zavala et al, 2013;Prasifka et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to Hall et al (2020), eCO 2 could also cause alterations in plant resource allocation and hormone production (e.g., jasmonic and salicylic acid). These changes may increase the production of secondary metabolites with allelochemical functions (Zavala et al, 2013;Oki et al, 2020), such as flavonoids (Flv) and sesquiterpenoids, commonly found in Asteraceae species (Prasifka et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide fertilization has not affected the total phenols determined in chickpea leaves [ 18 ]. Leaf polyphenol concentrations found in two Cerrado native species, Baccharis dracunculifolia and B. platypoda , grown at 400 ppmv and 800 ppmv carbon dioxide, have not been statistically significant [ 19 ].…”
Section: Introductionmentioning
confidence: 99%